2019
DOI: 10.1029/2018gl080634
|View full text |Cite
|
Sign up to set email alerts
|

Deglacial to Holocene Ocean Temperatures in the Humboldt Current System as Indicated by Alkenone Paleothermometry

Abstract: The response of the Humboldt Current System to future global warming is uncertain. Here we reconstruct alkenone‐derived near‐surface temperatures from multiple cores along the Peruvian coast to infer the driving mechanisms of upwelling changes for the last 20 kyr. Our records show a deglacial warming consistent with Antarctic ice‐core temperatures and a Mid‐Holocene cooling, which, in combination with other paleoceanographic records, suggest a strengthening of upwelling conditions. This cooling, during the glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 59 publications
(160 reference statements)
9
15
0
1
Order By: Relevance
“…6). Nevertheless, both Holocene records of cores 59-1 and 52-2 suggested a trend of increasing bottom-water oxygenation that is in accordance with recently published results from the region (Salvatteci et al, 2016(Salvatteci et al, , 2018Mollier-Vogel et al, 2019). Moreover, it is possible that bottom waters became more oxic after the late Holocene as reported for the shelf during the last 100-150 years (Cardich et al, 2019).…”
Section: Peruvian Margin Oxygen History Since the Lgmsupporting
confidence: 90%
“…6). Nevertheless, both Holocene records of cores 59-1 and 52-2 suggested a trend of increasing bottom-water oxygenation that is in accordance with recently published results from the region (Salvatteci et al, 2016(Salvatteci et al, , 2018Mollier-Vogel et al, 2019). Moreover, it is possible that bottom waters became more oxic after the late Holocene as reported for the shelf during the last 100-150 years (Cardich et al, 2019).…”
Section: Peruvian Margin Oxygen History Since the Lgmsupporting
confidence: 90%
“…Besides, large standard deviations observed in the northernmost core 59-1 raised questions about the applicability of the method for the Holocene (Figure 6). Never-the-less; both Holocene records of core 59-1 and 52-2, suggested a slight recovery of the OMZ that is in accordance with recently published results from the region (Salvatteci et al, 2016;Salvatteci et al, 2018;Mollier-Vogel et al, 2019). Since the records are not continuous, we cannot constrain changes in [O2]BW after the late Holocene.…”
Section: Peruvian Margin Oxygen History Since the Lgmsupporting
confidence: 82%
“…Both archaeological proxy-based EN reconstructions may be correct, reflecting the presence of a long-term climate divide at ∼12°S. The SST pattern of COA is consistent with multiple lines of evidence (16)(17)(18)(19)(20) for this divide. Hu et al (32) identified 7 COA events between 1979 and 2017.…”
Section: Discussion: Holocene En In Peru From Archaeological Proxiessupporting
confidence: 64%
“…The coast exhibits a significant climate divide at about 12°S (e.g., refs. [16][17][18][19][20], with coastal oceanographic and climate changes more pronounced to the north. During normal (non-EN) years, the Peru Current flows north along the Chilean and Peruvian coasts, bringing cool, deep, nutrient-rich water to the surface through intense upwelling; under these conditions, the thermocline is near the surface.…”
Section: P 3)mentioning
confidence: 99%